Comparative transcriptome analysis of Portunus trituberculatus in response to Vibrio parahaemolyticus and low salinity - Li, Yukun; Lv, Jianjian; Wu, Jie; Liu, Ping; Gao, Baoquan (Frontiers in Marine Science, 2022)
Vibrio parahaemolyticus is a common pathogen of marine crustaceans and is responsible for large losses in aquaculture. Salinity is an important environmental factor, and abrupt changes in salinity can affect the immunity of crustaceans. In this study, we carried out a transcriptomic analysis under pathogenic infection and low salt stress, and conducted a comparative analysis of the differentially expressed genes (DEGs) after stimulation by the two factors. Illumina sequencing technology was used for the transcriptome sequencing of 39 hepatopancreas samples, and 178.77 G sequencing data and an average of 44,142,119 clean reads per sample were obtained. A total of 3,047 and 3,710 DEGs were found after V. parahaemolyticus infection and low salt stress, which included a number of innate immunity genes, such as Toll-like receptor (TLR), anti-lipopolysaccharide factor (ALF), lectin, and hemocyanin. In addition, 2,016 common DEGs were found, accounting for 42.52% of the total DEGs. Among these, 169 DEGs were up-regulated after pathogenic infection and down-regulated after low salt stress, and were mainly enriched in starch and sucrose metabolism, nitrogen metabolism, amino sugar and nucleotide sugar processes, and other pathways. Collectively, these results provide data support for the analysis of the immune mechanism of crabs against V. parahaemolyticus and will also help to clarify the molecular mechanism by which salinity affects immunity.